Implementasi Kajian Kitab Kuning Metode Amtsilati dalam Mengembangkan Pendidikan Karakter Abad 21 di Pesantren - Fitriyah, Farihatil; Faizin, Moh.; Syafi'i, Imam (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
21st century character skills consist of critical thinking, creativity, communication and collaboration skills known as 4C skills. This study aims to explain the implementation of the yellow book study of the amtsilati method in developing 21st century character education at As-Shofiah Islamic boarding school. Amtsilati is a method that functions to read Arabic writing quickly and accurately, even though there is no harakat. This study discusses 21st century character education, the study of the yellow book of the amtsilati method and the implementation of the study of the yellow book of the amtsilati method in developing 21st century character education. The method used in this research is qualitative with descriptive type. Data was obtained through observation, interviews, documentation, questionnaires and library research. The results of this study indicate that the implementation of the study of the yellow book of the amtsilati method can develop 21st century character education at the As-Shofiah Islamic boarding school, especially in communication skills. This can be shown at the graduation ceremony in formal education, namely at MTsN 1 Sumenep, students who study the yellow book are chosen to appear to read the yellow book called the Amsilati Demonstration.